MOTIVASI BELAJAR SISWA KELAS V SDN GUGUS V AMPENAN PADA MASA PANDEMI COVID-19 - Dyah Ayu Lestari; Asrin Asrin; Heri Setiawan; I Nyoman Karma (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2022)
The purpose of this study is to find out how the motivation to learn on pandemic covid-19 for grade V students at SDN Cluster V Ampenan. The type of research used in this study is quantitative descriptive research with survey research methods. Data collection techniques used are questionnaires and documentation. The questionnaire used in this study serves to find out how the motivation of learning students during covid-19 in a predetermined sample, while the documentation is used to obtain data on the number of students and the list of names of grade V students at SDN Cluster V Ampenan. The study subjects were 121 respondents obtained by simple random sampling techniques. The data is analyzed using descriptive statistics. The results showed that the average overall percentage score obtained from the percentage score of each indicator of learning motivation is 78.17% included in the high category, it can be concluded that the motivation to learn on pandemic covid-19 for grade V students at SDN Cluster V Ampenan is relatively high.